Тheater as a synthesis of arts (Journal of Philosophy Culture and Political Science, 2019)
In the article the role of theatre is examined in society and in life of humanity on the whole, its today and past. The detailed elucidation of term «theatre» is given. In particular, his place is illuminated in the field of culture. The question of history of becoming a theatre is affected. There is told about the today’s achievements of dramatic art and the contribution to the culture of people.Analyzed the origins of this spirituality of young people, where their priceless wealth, happiness and values, art, design and culture through the sources, from generation to generation. And also, to raise the flag of independence, democratic civilized society, stretching out hands, theaters, carried out during the period of deepening reforms in all spheres of the country’s life, state, analysis and determination of the main directions for the realization of its culture will discuss a number of tasks solved in accordance with the real situation.If you deeply study the history of the theater, it is known that there will be no innovations in this area. That is why in the years since independence, it was noted that recapturing the sense of Khan’s identity contributed to the development of our art’s past and present.Key words: Theatre, culture, art, history, people, national, sovereign, stage, spectator, play.